2007
DOI: 10.1002/cvde.200606576
|View full text |Cite
|
Sign up to set email alerts
|

Incubation Effects upon Polycrystalline Silicon on Glass Deposited by Hot‐Wire CVD

Abstract: A growth mechanism diagnosis for high-rate, polycrystalline silicon deposition using hot-wire CVD is explored in this article. The effects of various deposition parameters on the Si film growth are investigated by Raman spectroscopy and transmission electron microscopy (TEM) measurements, with special attention paid to the crystalline and amorphous phases. It is found that the H 2 /SiH 4 ratio and substrate temperature (T s ) are the essential process parameters in determining the crystalline phase and the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It is shown that crystallinity of the film prepared using carbonized Ta is slightly less than that prepared by uncarbonized Ta at each temperature. As is well known, the crystallinity of Si film usually increases with the thickness during the growth [35,36]. Herein, the less thickness of the film prepared by carbonized Ta catalyst, as will be shown later, is also believed to be responsible for the little less crystallinity.…”
Section: Resultsmentioning
confidence: 74%
“…It is shown that crystallinity of the film prepared using carbonized Ta is slightly less than that prepared by uncarbonized Ta at each temperature. As is well known, the crystallinity of Si film usually increases with the thickness during the growth [35,36]. Herein, the less thickness of the film prepared by carbonized Ta catalyst, as will be shown later, is also believed to be responsible for the little less crystallinity.…”
Section: Resultsmentioning
confidence: 74%
“…The Ge-Ge Raman peak of the top surface layer shifts 5 cm −1 towards lower frequency, whereas the shift is only about 1 cm −1 for the bottom part. Several reasons, such as phonon confinement, stress and polycrystallinity, can shift the Ge-Ge optical phonons [30,31]. Compressive stress leads to an upward shift of the Ge-Ge mode, while a, b, d) and the glass substrate (c).…”
Section: Raman Scatteringmentioning
confidence: 99%
“…As for polycrystallinity, it may result in inhomogeneous broadening (with low frequency tailing) and minor peak shifts [31,36,37]. The effect of stress on Raman shift can be changed by stress relaxation using post-annealing [38][39][40].…”
Section: Raman Scatteringmentioning
confidence: 99%
“…Details of the deposition conditions and properties of all silicon films (n-Si, i-Si and p-Si) were summarized in our earlier report. [24][25][26][27] The solar cell (1 Â 1 cm 2 ) characteristics such as short circuit current density J sc , open circuit voltage V oc , fill factor FF, conversion efficiency h, and external quantum efficiency EQE were measured at 100 mW/cm 2 (AM 1Á5) using a solar simulator.…”
Section: Hwcvd Fabricationmentioning
confidence: 99%
“…Figure 6 shows the dependency of solar cell parameters on the crystallinity of the n-layer and i-layer for the simplest cell structure. The crystallinity of undoped or doped mc-Si films can be controlled by changing the hydrogen dilution, the substrate temperature, and the filament temperature (see our early report 25 ). The solar cells with n-layer/i-layer/c-Si structure were set for simulation in this object.…”
Section: Effect Of Silicon Film Crystallinitymentioning
confidence: 99%